Modulation of the electron transfer processes in Au-ZnO nanostructures - Aguirre, Matías Ezequiel (2015)
Plasmonic nanostructures comprising Au and ZnO nanoparticles synthesized by the spontaneous reduction of HAuCl4 in ethylene glycol were used to assess the possibility of modulating the direction of the electron transfer processes at the interface. One electron UV reduction and visible oxidation of the reversible couple TEMPOL/TEMPOL-H was confirmed by EPR spectroscopy. The apparent quantum yield for TEMPOL-H conversion under continuous wave visible excitation depends on the irradiation wavelength, being 0.57% and 0.27% at 450 ± 12 and 530 ± 12 nm, respectively. These results indicate that both the surface plasmon resonance and the interband transition from the 5d to the 6s level of Au nanoparticles contribute to the visible activity of the nanostructure. In addition, by detecting free electron conduction band electrons in ZnO, after the visible excitation of Au/ZnO nanostructures, we provide direct evidence of the photoexcited electron transfer from gold nanoparticles to ZnO.